2003
DOI: 10.1002/mrm.10456
|View full text |Cite
|
Sign up to set email alerts
|

Water diffusion measurements in perfused human hippocampal slices undergoing tonicity changes

Abstract: Diffusion MRI has the potential to probe the compartmental origins of MR signals acquired from human nervous tissue. However, current experiments in human subjects require long diffusion times, which may confound data interpretation due to the effects of compartmental exchange. To investigate human nervous tissue at shorter diffusion times, and to determine the relevance of previous diffusion studies in rat hippocampal slices, water diffusion in 20 perfused human hippocampal slices was measured using a wide-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…Cell swelling induces changes of the extracellular tortuosity and, hence, to the ADC [9,10]. Our model predicts that an extracellular tortuosity of ϳ1.4 is associated with normal levels of ADC, as depicted in Fig.…”
Section: Cell Volume and Restrictionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cell swelling induces changes of the extracellular tortuosity and, hence, to the ADC [9,10]. Our model predicts that an extracellular tortuosity of ϳ1.4 is associated with normal levels of ADC, as depicted in Fig.…”
Section: Cell Volume and Restrictionmentioning
confidence: 71%
“…The volume fractions did not agree with the fractions expected from histology (i.e., slow-diffusing intracellular fraction of ϳ80% and fast-diffusing extracellular fraction of ϳ20%). In the study by Shepherd et al (10), (using perfused human hippocampal slices) a distinct difference between the slow-and the fast-diffusion coefficient was shown using biexponential diffusion analysis, where the fast-diffusing component was ascribed to the largest cellular fraction. Similarly, Inglis et al (11) found the slow-and fast-diffusion components to be 44% and 56%, respectively, while spectroscopic T 2 relaxation measurements yielded volume fractions of 17% and 83% with values of 41 msec and 94 msec, respectively.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9] These values represent a paradoxical reversal of what may be anticipated for the volume fractions if one assigns the fast diffusion coefficient component to the extracellular water and the slow diffusion coefficient component to the intracellular water. 38 However, even if these volume fractions appear to be opposite of what they should be for extra-and intracellular water, the direction of the change of the apparent volume fractions which have accompanied physiological manipulations of the actual intra-and extracellular compartments by stroke, 8 osmotic or pharmacological manipulation, 6,7 and development from newborn to adult, 5 have actually been consistent with this simple assignment. Indeed, using the Karger equations for a two-compartment model, which includes the effects of water exchange, 35 it is possible to consider moderate exchange rates.…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3][4][5][6] The assignment of the fast and slow tissue water diffusion components to extra-and intracellular water, respectively, has been discussed, if not universally espoused, as a possibility in these [1][2][3][4][5][6] and several other related works. [7][8][9][10][11][12][13][14][15] This assignment remains intriguing but controversial since restricted diffusion effects alone can lead to decay curves which appear to be biexponential in form but do not require an underlying assumption of two or more distinct water compartments. [15][16][17][18][19][20][21][22] We hypothesize that if the physical basis of empirically useful biexponential decay analyses is two distinct water compartments with widely disparate diffusion coefficients, then it would reasonably follow that the two compartments might have substantially different magnetization transfer ratios.…”
Section: Introductionmentioning
confidence: 95%
“…The b-values for the PRE are obtained by using T M ϭ 0 and replacing ⌬ STE with ⌬ PRE in Eqs. [11] and [12]. Sequence parameters are taken from Table 1.…”
Section: Diffusion Weighting Due To Susceptibility Variations Of Venomentioning
confidence: 99%